Salvage radiofrequency ablation followed by external beam radiotherapy for inoperable recurrent differentiated thyroid cancer - Chung-Shih Chen; Sheng-Dean Luo; Yen-Hsiang Chang; Chen Kai Chou; Shun-Yu Chi; Shao-Chun Wu; Yen-Hao Chen; Johnson Chia-Shen Yang; Eng-Yen Huang; Yu-Ming Wang; Wei-Che Lin (International Journal of Hyperthermia)
Purpose The treatment of recurrent thyroid cancer with critical organ invasion is challenging. The combination of radiofrequency ablation (RFA) and external beam radiation therapy (EBRT) has been proposed as an effective option. This study evaluates outcomes for inoperable residual/recurrent differentiated thyroid cancer (rDTC) patients treated with RFA followed by EBRT.Materials and Methods Patients with rDTC treated with RFA followed by EBRT were retrospectively studied. RFA was performed using a free‐hand, ‘moving‐shot’ technique under US or CT guidance. For lesions invading critical structures intolerant to ‘en bloc’ high-temperature RFA, limited-field EBRT using 6‐ or 10‐MV photons was used for adjuvant treatment at a dose of 66 Gy in 33 daily fractions. Toxicities and outcomes were reviewed.Results Between April 2020 and January 2022, 11 patients with 14 rDTC lesions underwent RFA followed by EBRT. Five patients had metastatic lesions at rDTC diagnosis. With a median follow-up period of 33.7 months, all patients maintained locoregional control, while achieving a 2-year survival rate of 90.9%. This combined treatment achieved a volume reduction ratio of 92.1% ± 5.1%. The mean nadir thyroglobulin level in patients without initial distant metastases after treatment was 1.40 ± 0.81 ng/ml. Regarding treatment-related complications, one patient (9%) experienced temporary hoarseness after RFA, grade 2 radiation dermatitis occurred in 3 patients (27.2%), and grade 2 dysphagia was noted in 4 patients (36.4%). No grade 3 or greater toxicities occurred.Conclusions Salvage RFA followed by EBRT is feasible, effective and safe for patients with rDTC.